Margaropus Karsch, 1879 is not closely related to Boophilus Curtice, 1891 (Acari: Ixodidae) - Barker, Stephen C.; Kelava, Samuel; Murrell, Anna; Cho, Mingeun; Teo, Ernest J. M.; Nakao, Ryo; Apanaskevich, Dmitry A. (Zootaxa, 2025)
Margaropus Karsch, 1879 and Boophilus Curtice, 1891 have been thought to be sister-taxa for over 75 years since these ticks share features like circular spiracles, no festoons, no distinct grooves behind the anus and one-host life cycles. We inferred the first phylogeny with Margaropus from 4,218 bp of mitochondrial (cox 1, 12S) and nuclear DNA (ITS2, 18S rRNA). Margaropus is not the sister-group to Boophilus or even closely related to Boophilus, but rather Margaropus is either the sister-group to, or embedded in, the genus Rhipicephalus.